Microbial divergence and evolution. The case of anammox bacteria - Cuecas, Alba; Barrau, M. Julia; Gonzalez, Juan M. (Frontiers in Microbiology, 2024)
Species differentiation and the appearance of novel diversity on Earth is a major issue to understand the past and future of microbial evolution. Herein, we propose the analysis of a singular evolutive example, the case of microrganisms carrying out the process of anammox (anaerobic ammonium oxidation). Anammox represents a singular physiology active on Earth from ancient times and, at present, this group is still represented by a relatively limited number of species carrying out a specific metabolism within the Phylum Planctomycetota. The key enzyme on the anammox pathway is hydrazine dehydrogenase (HDH) which has been used as a model in this study. HDH and rRNA (16S subunit) phylogenies are in agreement suggesting a monophyletic origin. The diversity of this singular phylogenetic group is represented by a few enriched bacterial consortia awaiting to be cultured as monospecific taxa. The apparent evolution of the HDH genes in these anammox bacteria is highly related to the diversification of the anammox clades and their genomes as pointed by phylogenomics, their GC content and codon usage profile. This study represents a clear case where bacterial evolution presents a paralleled genome, gene and species diversification through time from a common ancestor; a scenario that most times is masked by a web-like phylogeny and the huge complexity within the prokaryotes. Besides, this contribution suggests that microbial evolution of the anammox bacteria has followed an ordered, vertical diversification through Earth history and will present a potentially similar speciation fate in the future.